ETOS KERJA NELAYAN DI KELURAHAN TELUK MERBAU KECAMATAN KUBU KABUPATEN ROKAN HILIR - Erwan "; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research was conducted in the Teluk Merbau Village, Kubu District Rokan Hilir Regency. This area was chosen because the welfare level of fishing families in this community is still low and there are various characteristics of different levels of education, economic status, and employment. The purpose of this study was to look at the work ethic of fishermen in Merbau Bay District Kubu District Rokan Hilir Regency and the factors that influence it. The population in this study were fishermen in the Merbau Bay District Kubu District Rokan Hilir Regency were 136 fishermen. Sampling using simple random sampling technique using Slovin formula which obtained a sample size of 58 fishermen. Analysis of the data used is descriptive quantitative. The results of the study found that the economic condition in the Merbau Bay District Kecanatan Kubu was quite good, while the effort to improve the economy of the fishing community was to provide it with modern fishing gear. The work ethic of fishermen who are already considered good can be seen from the many fishermen who are disciplined in working, high levels of work skills, the level of work motivation of fishermen who are very sting, and high morale of the fishermen. The factors that influence the work ethic of fishermen are changing lives for the better, having a good relationship with the buyers, and having high morale. Keywords: Work Ethic and Fisherman